NF‐κB and HIF crosstalk in immune responses - D'Ignazio, Laura (FEBS J, 2015)
Hypoxia and inflammation have been associated with a number of pathological conditions, in particular inflammatory diseases. While hypoxia is mainly associated with the activation of hypoxia‐inducible factors (HIFs), inflammation activates the family of transcription factor called nuclear factor‐kappa B (NF‐κB). An extensive crosstalk between these two main molecular players involved in hypoxia and inflammation has been demonstrated. This crosstalk includes common activating stimuli, shared regulators and targets. In this review, we discuss the current understanding of the role of NF‐κB and HIF in the context of the immune response. We review the crosstalk between HIF and NF‐κB in the control of the immune response in different immune cell types including macrophages, neutrophils and B and T cells. Furthermore the importance of the molecular crosstalk between HIFs and NF‐κB for a variety of medical conditions will be discussed.